Optimale Regelung eines prädiktiven Energiemanagements von Hybridfahrzeugen - Wahl, Hans-Georg (KIT Scientific Publishing, 2021)
This work combines the current trends in automotive industries (E-mobility, autonomous driving and connected car) in a new design of a driver assistance system for Hybrid Electric Vehicles that overtakes the speed control as well as the control of the energy management.